Addison-Wesley's Real world math adventures in flight. (San Mateo, CA : Sanctuary Woods, 1994)
Users are introduced to math concepts in an imaginary trip to the airport where they help employees from pilots to baggage handlers apply math skills on the job.
Title from disc label.
Production level cataloging.
Ages 7 to 11.
System requirements: Macintosh LCIII or higher; System 6.07 or later.
Keywords: Mathematics -- Study and teaching (Elementary) -- Juvenile software; Mathematics; Mathematical recreations